Understanding Residents’ Physical Activity Intention and Behavior Amid COVID-19 Pandemic - Cheng, Xiaoyu; Chen, Wei (Frontiers in Psychology, 2022)
Proper and regular physical activity plays an important role in improving people's health. With the outbreak of the COVID-19 pandemic which has posed a serious threat to individual health, residents' physical activity has been aroused deep concern. Based on the theory of planned behavior, this paper examines the impact of residents' physical activity intention and behavior in response to the COVID-19 pandemic. Data were collected from a sample of 961 residents in Wuhan in China by questionnaire survey. The data results show that, residents' physical activity intention and behavior have been affected significantly by residents' physical activity attitude, subjective norms, and perceived behavioral control. The COVID-19 pandemic has a significant impact on both residents' physical activity intention and behavior. In addition, there were gender and region differences in this impact. The findings are of great significance in promoting residents' physical activity intention and physical activity behavior, which are of positive significance to the development of residents' physically and mentally healthy in the period of global serious health crisis.